2014
DOI: 10.1097/aap.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Observer-Blinded Study to Assess Postoperative Analgesia Provided by an Ultrasound-Guided Bilateral Thoracic Paravertebral Block for Children Undergoing the Nuss Procedure

Abstract: Ultrasound-guided BTPV block provides improved postoperative analgesia for children undergoing the Nuss procedure as compared with intravenous PCA and decreases the incidence of postoperative behavioral disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…Therefore, these blocks are often underutilized despite potential benefits with regard to patient outcomes. Qi et al30 evaluated the effectiveness of an ultrasound-guided bilateral thoracic paravertebral block for postoperative pain control in children undergoing the Nuss procedure, and showed that the ultrasound-guided bilateral thoracic paravertebral block improved postoperative analgesia compared with PCIA and decreased the incidence of postoperative behavioral disturbance. The use of ultrasound guidance provides real-time information about the needle tip location and local anesthetic delivery to the desired location,31 which has also been demonstrated to improve success rates for ilioinguinal and transversus abdominis plane blocks, decrease the volume of local anesthetic solution, and avoid inadvertent needle trauma to surrounding structures 12,32.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these blocks are often underutilized despite potential benefits with regard to patient outcomes. Qi et al30 evaluated the effectiveness of an ultrasound-guided bilateral thoracic paravertebral block for postoperative pain control in children undergoing the Nuss procedure, and showed that the ultrasound-guided bilateral thoracic paravertebral block improved postoperative analgesia compared with PCIA and decreased the incidence of postoperative behavioral disturbance. The use of ultrasound guidance provides real-time information about the needle tip location and local anesthetic delivery to the desired location,31 which has also been demonstrated to improve success rates for ilioinguinal and transversus abdominis plane blocks, decrease the volume of local anesthetic solution, and avoid inadvertent needle trauma to surrounding structures 12,32.…”
Section: Discussionmentioning
confidence: 99%
“…It contains six domains: general anxiety, aggression toward authority, separation anxiety, eating disturbance, sleep anxiety, apathy, and withdrawal. In our study, we used the translated version of the PHBQ, which has been widely used in research . We scored the PHBQ using two methods .…”
Section: Methodsmentioning
confidence: 99%
“…No complications from placing TPVBs were noted in the study. They concluded that ultrasound-guided bilateral TPVBs provide improved postoperative analgesia for children undergoing the Nuss procedure as compared with intravenous parent-controlled intravenous analgesia and decreased the incidence of postoperative behavioral disturbance [17].…”
Section: Thoracic Paravertebral Blocks For Pectus Excavatum Repairmentioning
confidence: 99%